2016
DOI: 10.4081/hls.2015.5411
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial stressors and support needs of survivors of Ebola virus disease, Bombali District, Sierra Leone, 2015

Abstract: Ebola virus disease (EVD) survivors are increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…While not common, some EVD survivors did experience rejection by their family members. Studies from Sierra Leone and Guinea reported such rejection in 4/299 (1.3%) and 8/105 (7.6%) EVD survivors respectively. There was less acceptance by their friends, with a larger proportion of EVD survivors 102/105 (97.1%) identifying that they were rejected by their friends in Guinea .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…While not common, some EVD survivors did experience rejection by their family members. Studies from Sierra Leone and Guinea reported such rejection in 4/299 (1.3%) and 8/105 (7.6%) EVD survivors respectively. There was less acceptance by their friends, with a larger proportion of EVD survivors 102/105 (97.1%) identifying that they were rejected by their friends in Guinea .…”
Section: Resultsmentioning
confidence: 99%
“…The remaining three were cohort studies. Eighteen studies were from the 2013 to 2016 outbreak in West Africa the remaining six are from 1995 to 2012 outbreaks in Eastern Africa . Of the 24 papers, 23 were published in English and one published in French .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations